South Pacific - Hammerstein, Oscar 1895-1960; Rodgers, Richard 1902-1979; Gaynor, Mitzi 1930-; Brazzi, Rossano 1916-; Logan, Joshua; Adler, Buddy 1906-1960
Romance on the South Seas set against the backdrop of a world at war.